29 Management of Heart Failure following Primary PCI after ST-Elevation Myocardial Infarction: A Large UK Tertiary Centre Experience. (6th June 2015) - Boles, Sophie; Wood-Gismera, Scarlett; Dastidar, Amardeep Ghosh; Ismail, Yasmin; Bucciarelli-Ducci, Chiara; Nightingale, Angus
Abstract : Background: Heart failure (HF) is a common complication following an ST-elevation myocardial infarction (STEMI). This is associated with significant morbidity and mortality despite successful and timely primary percutaneous coronary intervention (PPCI). Therefore, it is imperative that patients who develop left ventricular systolic dysfunction (LVSD) are treated appropriately. The NICE guidelines recommend that patients with an ejection fraction (EF) </=40% with signs or symptoms of HF should be started on an aldosterone antagonist (AldA). However, the discrepancy between the guidelines and clinical practice is uncertain. Aims: To evaluate the: Prevalence of LVSD following PPCI Difference between the length of hospital stay and mortality rate in patients with and without LVSD Factors associated with the development of HF Compliance with NICE guidelines for the prescription of an AldA. Methods: We conducted a retrospective observational study in a tertiary centre in the South West of England, involving all STEMI patients who underwent PPCI between January to December 2013. LVSD was defined as an EF </=40%, as obtained from echocardiography or cardiac MRI. Fisher's Exact Tests and Mann-Whitney U Tests were used to establish statistical significance. P value of <0.05 was considered significant. Results: Of the 573 patients who underwent PPCI, 74% were male and the median age was 64 years. 9 patients died prior to formal assessment of left ventricular function and were excluded from further analysis. 42% (n = 231) of patients with a recorded EF had LVSD. Such patients had a significantly greater median length of hospital stay (4 vs 3, P < 0.0001) and 30-day mortality rate (17 vs 9, P = 0.01). Patients with LVSD also had a significantly higher peak troponin level (5981 vs 2816, P < 0.0001) and were more likely to have the left anterior descending (LAD) as their culprit artery (138 vs 104, P < 0.0001) than patients without LVSD. 84% (n = 193) of patients with LVSD qualified for an AldA; however, only 47% (91/193) of these patients received this medication. Conclusion: Heart failure is a frequent complication of STEMI and is associated with a significantly increased mortality and length of hospital stay. Inpatient echocardiography for PPCI patients is crucial to identify those who would benefit from AldA therapy. Patients with LVSD were more likely to have a higher troponin level and an LAD culprit artery. These findings emphasise the need for good liaison between ACS and Heart Failure services both in hospital and on discharge. Compliance with NICE guidelines could be improved for this vulnerable group of high risk patients.